2010
DOI: 10.1177/0269216310378784
|View full text |Cite
|
Sign up to set email alerts
|

‘Heated political dynamics exist …’: examining the politics of palliative care in rural British Columbia, Canada

Abstract: Palliative care is delivered by a number of professional groups and informal providers across a range of settings. This arrangement works well in that it maximizes avenues for providing care, but may also bring about complicated 'politics' due to struggles over control and decision-making power. Thirty-one interviews conducted with formal and informal palliative care providers in a rural region of British Columbia, Canada, are drawn upon as a case study. Three types of politics impacting on palliative care pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Their lack of consistent information, support, and advocacy made enacting their responsibilities as care providers more challenging. Our findings support those of others who have suggested that the politics related to control and decision making that play out in rural palliative care can lead to lower quality care (Crooks et al, 2011). Further, if morality is born out of shared understandings of “assigning, accepting, and deflecting responsibility” (Urban Walker, 2007, p. 235) then confusion of responsibilities can lead to moral distress.…”
Section: Discussionsupporting
confidence: 91%
“…Their lack of consistent information, support, and advocacy made enacting their responsibilities as care providers more challenging. Our findings support those of others who have suggested that the politics related to control and decision making that play out in rural palliative care can lead to lower quality care (Crooks et al, 2011). Further, if morality is born out of shared understandings of “assigning, accepting, and deflecting responsibility” (Urban Walker, 2007, p. 235) then confusion of responsibilities can lead to moral distress.…”
Section: Discussionsupporting
confidence: 91%
“…4,5,12 Although the literature also recognises the benefits of interdisciplinary team-working, a recognised strength of palliative care, it identifies that effective IDTs must also have the desire to work together to achieve a common goal, which provides a holistic and patient-focused approach to disease management. 8,17,36 It is this need for diversity in team-working, which can be a barrier to effective interdisciplinary collaboration, 14,29,37 in particular, the impact of professional culture.…”
Section: Barriers To Effective Interdisciplinary Collaboration: Profementioning
confidence: 99%
“…Chan and Nichols 16 also supported the guidelines by recognising that team-working is an essential component to providing an effective holistic approach to care, which has increased quality of life for patients. Having a healthcare team that is diverse in its composition of providers and services enables provision of care that is responsive to a range of ongoing and changing patient care needs 17 . The IDT approach has also been noted as being a cost-effective method to providing care in a demanding healthcare system while creating a holistically caring environment 18 …”
Section: Interdisciplinary Collaboration and Holismmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted 31 semi-structured interviews with key informants in the BC communities of Trail, Nelson, and Castlegar. We pursued a number of qualitative analyses that assisted with better understanding the scope of palliative care need in rural BC and the implications of this for our siting model [see 34 , 35 , 39 , 40 ]. Of relevance to the current article, it became apparent from the interview findings that an important additional factor needed to be added into the siting model: community readiness.…”
Section: Introductionmentioning
confidence: 99%